The expression regulation of recA gene and bacterial class 2 integron-associated genes induced by antibiotics - Ye, Jinglu; Sun, Qian; Wu, Qiaoping; Xu, Jianqiang; Yang, Ye; Zhao, Rongqing; Li, Qingcao (Frontiers in Microbiology, 2025)
ObjectiveTo investigate the effects and mechanisms of common antibiotics induction on the expression of class 2 integron integrase and variable region resistance genes in bacteria, as well as potential structural mutations.MethodsClinical isolates containing non-functional class 2 integrons and functional class 2 integrons were selected. Strains containing non-functional class 2 integrons or functional class 2 integrons were constructed using isolated DNA templates. These strains were subjected to continuous induction with drug concentrations of 1/2 MIC and 1/4 MIC (ciprofloxacin, ampicillin, and kanamycin) and a concentration of 0.2 μg/ml (mitomycin C) over 8 days. The relative expression levels of relevant genes were measured on days 1, 3, and 8. Drug resistance in the experimental strains was assessed before and after induction to identify any differences. Finally, the sequence of the non-functional class 2 integron integrase gene was analyzed for structural changes that occurred as a result of induction.ResultsAll drugs selected in this study increased the relative expression levels of recA, intI2, dfrA1, sat2, and aadA1. Significant differences in inductive abilities were observed among the drugs. The 1/2 MIC concentrations were more effective than 1/4 MIC concentrations in increasing the relative expression levels of target genes and enhancing the resistance of the experimental strains. The relative expression levels of recA, intI2, and dfrA1 rose on day 1, peaked on day 3, and slightly declined by day 8. Induced strains exhibited increased resistance to the drugs, with the most significant changes observed in the clinical isolates, particularly concerning CIP resistance. Notably, clinical isolate 7b induced with 1/2 MIC KAN exhibited the loss of one base at position 12bp in the integrase sequence. However, none of the four drugs induced mutations at the 444 bp position of class 2 integrons.ConclusionSub-MIC concentrations of drugs have been shown to induce an increase in the relative expression level of the SOS response-related gene recA, as well as the integrase and resistance genes of class 2 integrons. Continuous induction leads to sustained upregulation of these genes, which stabilizes or slightly decreases upon reaching a plateau. However, the capacity of different drugs to induce expression varies significantly. Short-term antibiotic exposure did not result in critical mutations that convert class 2 integrons into functional forms.